Outcome of Acute Subdural Hematoma: Conservative vs Surgical Management - Muhammad Imran Khan, Muhammad Jahangir Khan, Sajjad Ali, Safia Bano, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Acute subdural hematoma is a life-threatening consequence of traumatic brain injury and is associated with high morbidity and mortality. Objective: To compare outcomes of acute subdural hematoma managed conservatively versus surgically and identify factors associated with prognosis. Methods: This descriptive, comparative, cross-sectional study was conducted at Department of Neurology, Sialkot Medical College, Sialkot from 1st March 2023 to 31st August 2023, 110 patients diagnosed with acute subdural hematoma were included. Patients were categorized into conservative and surgical management groups based on clinical and radiological criteria. Data collected included demographic characteristics, admission Glasgow Coma Scale, computed tomography scan findings, management details, hospital course, and outcomes measured using the Glasgow Outcome Scale (GOS). Results: Patients managed surgically presented with significantly lower admission Glasgow Coma Scale scores and greater radiological severity, including higher hematoma thickness and midline shift. The conservative group had a higher proportion of favourable outcomes (70.8%) compared to the surgical group (51.6%), reflecting milder initial injury. Overall mortality was 9.1% and was strongly associated with admission Glasgow Coma Scale ≤8, midline shift ≥5 mm, advanced age, and need for ventilator support. Surgically managed patients required longer intensive care unit and hospital stays and had higher complication rates, consistent with greater injury severity at presentation. Conclusion: The outcomes in acute subdural hematoma are primarily determined by initial neurological status and radiological severity rather than treatment modality alone. Keywords: Acute subdural hematoma, Conservative management, Surgical management, Glasgow Coma Scale, Traumatic brain injury